2012
DOI: 10.1136/annrheumdis-2012-201381
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of interferon type I signature in CD14 monocytes of patients with Sjögren's syndrome and association with disease activity and BAFF gene expression

Abstract: ObjectiveTo determine the prevalence of upregulation of interferon (IFN) type I inducible genes, the so called ‘IFN type I signature’, in CD14 monocytes in 69 patients with primary Sjögren's syndrome (pSS) and 44 healthy controls (HC) and correlate it with disease manifestations and expression of B cell activating factor (BAFF).MethodsExpression of IFI44L, IFI44, IFIT3, LY6E and MX1 was measured using real time quantitative PCR in monocytes. Expression values were used to calculate IFN type I scores for each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
234
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(278 citation statements)
references
References 35 publications
31
234
4
2
Order By: Relevance
“…Increased BAFF levels seen in certain chronic autoimmune disorders and chronic inflammatory diseases were reported to be associated with an elevated type-I IFN response (51)(52)(53). Moreover, we reported that HIV-1-directed release of type-I IFN by pDCs plays a determinant role in BAFF production by monocytes (30).…”
Section: Hiv-1-mediated Baff Production In Mdms Is Independent Of Typmentioning
confidence: 84%
“…Increased BAFF levels seen in certain chronic autoimmune disorders and chronic inflammatory diseases were reported to be associated with an elevated type-I IFN response (51)(52)(53). Moreover, we reported that HIV-1-directed release of type-I IFN by pDCs plays a determinant role in BAFF production by monocytes (30).…”
Section: Hiv-1-mediated Baff Production In Mdms Is Independent Of Typmentioning
confidence: 84%
“…There are consistent reports that monocytes are contributing to the elevated of BAFF in SjS patients (8). Serum level of BAFF in SjS patients correlates with BAFF mRNA expression (2). Peripheral blood monocytes of SjS patients produce significantly higher amount of sBAFF in vitro both spontaneously and after stimulation with interferon γ (22).…”
Section: Discussionmentioning
confidence: 56%
“…[10] Initial microarray analysis of mRNA extracted from minor salivary gland tissue of pSS patients revealed an upregulated expression of many IFN-stimulated genes, the so-called IFN signature, compared to nonpSS sicca patients. [4,11] The finding that the increased expression of many (type I) IFN-stimulated genes can also been observed in circulating monocytes, peripheral blood mononuclear cells, and whole blood from pSS patients [12][13][14] indicates that IFN activity is clearly not only restricted to the target tissue itself, but is a more systemic feature of the disease. Possibly, continued activation of type I IFN production by triggers such as virus, autoantigen, and immune complexes in combination with a special genetic background and lack of proper control and regulation may be responsible for the observed overproduction of type I IFN in pSS patients.…”
Section: Editorialmentioning
confidence: 99%
“…Approximately 60% of the pSS patient have a high type I IFN score (signature) in blood based upon the expression of a few (2-5) type I IFN-stimulated genes or whole blood myxovirusresistance protein A levels. [10,14,18] A significant number (slightly less than half of these patients) concomitantly also have a type II IFN signature; only relatively few pSS patients (7%) exhibit only a type II IFN signature. [18] Based upon the expression of a single IFN-induced protein, Hall et al [17] observed that 17% of the patients demonstrated high type I IFN activity in the minor salivary glands, 21% high type II IFN activity, and 21% exhibited a mixed-type I/II IFN profile.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation